(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: After a period of increased malaria from July 2023, transmission was temporarily interrupted in early 2025 in Khanh Vinh. However, malaria returned mainly due to Plasmodium falciparum in May-June 2025, threatening the malaria elimination goal. Objective: To describe the resurgence and evaluate the changes in transmission dynamics of P. falciparum in Khanh Vinh during the post-control period Methods: A descriptive study based on retrospective data (2022-2025) and a cross-sectional study in Khanh Dong and Khanh Thuong communes in July 2025, focusing on high-risk groups. Clinical examination, Giemsa-stained blood smear microscopy, and structured interviews were used for assessment. Results: A total of 408 at-risk individuals were screened; 12 malaria cases (2.94%) were detected. The positivity rate was 4.57% in Khanh Thuong commune and 1.06% in Khanh Dong commune. Of the cases, 91.67% were caused by P. falciparum, 50% were asymptomatic, and 58.33% carried gametocytes; the geometric mean parasite density was 3,606 parasites/µl blood. P. falciparum was observed to cluster in Khanh Thuong, signalling a spatial shift in transmission. Conclusion: The increase and transmission shift of P. falciparum in Khanh Vinh, especially asymptomatic infections, threaten the malaria elimination goal. Enhanced surveillance and targeted interventions are required.